Adalimumab Treatment in Biologically Naïve Crohn's Disease: Relationship with Ectopic MUC5AC Expression and Endoscopic Improvement. (16th April 2014) - Mizoshita, Tsutomu; Tanida, Satoshi; Tsukamoto, Hironobu; Ozeki, Keiji; Katano, Takahito; Nishiwaki, Hirotaka; Ebi, Masahide; Mori, Yoshinori; Kubota, Eiji; Kataoka, Hiromi; Kamiya, Takeshi; Joh, Takashi
Abstract : Background . Adalimumab (ADA) is effective for patients with Crohn's disease (CD). However, there have been few reports on ADA therapy with respect to its relationship with pathologic findings and drug efficacy in biologically naïve CD cases. Methods . Fifteen patients with active biologically naïve CD were treated with ADA. We examined them clinically and pathologically with ectopic MUC5AC expression in the lesions before and after 12 and 52 weeks of ADA therapy, retrospectively. Results . Both mean CD activity index scores and serum C-reactive protein values were significantly lower after ADA therapy (P < 0.001 ). In the MUC5AC negative group, all cases exhibited clinical remission (CR) and endoscopic improvement at 52 weeks. In MUC5AC positive groups, loss of MUC5AC expression was detected in cases having CR and endoscopic improvement at 52 weeks, while remnant ectopic MUC5AC expression was observed in those exhibiting no endoscopic improvement and flare up after 52 weeks. Conclusions . ADA leads to CR and endoscopic improvement in biologically naïve CD cases. In addition, ectopic MUC5AC expression may be a predictive marker of flare up and endoscopic improvement in the intestines of CD patients.